(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo, non sottoposto a valutazione, riproduce, con l’aggiunta delle note, il testo della Relazione al Convegno di Studi, Ratio Juris Seminar, Genocide and Human Dignity. Hannah Arendt’s Moral Ontology (4 giugno 2014, Università degli Studi “Magna Graecia“ di Catanzaro, Dipartimento di Scienze Giuridiche, Storiche, Economiche e Sociali). SOMMARIO: 1. Premessa – 2. Breve analisi del problema dei punti di osservazione nell’attività conoscitiva 3. I punti di osservazione e l’“evento genocidio” – 4. Conclusione: il punto di osservazione giuridico. The Legal Definition of Genocide and the Problem of the Observation Points: Some Considerations about David Luban’s Perspective ABSTRACT: This brief paper concerns with the question of the legal definition ofgenocide, ie, and in more practical terms, with the problem about the opportunity of modifying “The Convention on the Prevention and Punishment of the Crime of Genocide” adopted by United Nations General Assembly in 1951, which is still today the standard legal definition of genocide. What I propose here, is to join and support the conclusions expressed by Professor Luban the 2006 article Calling Genocide by Its Rightful Name, but following a different line of argumentation.To this end, I intend to divide the paper in two parts: 1) in the first one I will carry out some general considerations about the problem ofknowledge, as a matter of definition. And in particular I will try to offer some guidance on the complex issue of the “observation points”, such as central elements of the activity of knowing and defining a particular object of knowledge. 2) In the second part I will try toapply these results to the question of “genocide” as a possible object of knowledge anddefinition.